Islam, Globalization, and Freedom of Expression - Muhammad Daiyabu Hassan (Journal of Global Initiatives, 2010)
The exercise of freedom of expression by a segment of the secular establishment, mainly among members of the literary and intellectual elite in the West, in relation to Islam, constitutes a major obstacle in the search for common grounds between the Islamic world and the West. Due to historical factors, the church seems to have assented to the continuous secular attacks on Christianity. Some examples in this regard are Dan Brown's Da Vinci Code and Martins Scorsese's film adaptation of Nikos Kazanstzaki's The Last Temptation of Christ. To this segment of Western secular cultural thinkers, nothing is sacred. The publication of a series of cartoons satirizing Prophet Muhammad by the Danish newspaper, Jyllad Posten, marked a new height in the secular assault on the taboos of Islam since the publication of Salman Rushdie's book The Satanic Verses in 1988. The various reactions this event engendered from across the Muslim world and the controversy that ensued, point to a new dimension on the strained relations between Islam and the West, shaped by interactions between forces of religion, globalization, and liberalism.